Family Araliaceae in Southern Africa: A Review of Ethnobotanical Uses, Phytochemistry, Pharmacology, and Toxicology - Maroyi, Alfred (Journal of Pharmacy and Nutrition Sciences, 2022)
There is widespread use of species belonging to family Araliaceae in traditional medicine in southern Africa. The aim of this review was to assess medicinal uses, phytochemistry, pharmacology and toxicological properties of indigenous species belonging to family Araliaceae in southern Africa. Relevant articles, books, theses, dissertations, patents, and other English-only reports on the medicinal uses, phytochemistry, pharmacological and toxicological properties of species belonging to the family Araliaceae in southern Africa (Angola, Botswana, Eswatini, Lesotho, Malawi, Mozambique, Namibia, South Africa, Zambia and Zimbabwe) were reviewed. Databases such as PubMed, Web of Science, Elsevier, Google Scholar, Scopus, Springer, Science Direct, Taylor and Francis between January and July 2022. Eleven species, namely Cussonia. arborea, C. arenicola, C. natalensis, C. nicholsonii, C. paniculata, C. sphaerocephala, C. spicata, C. transvaalensis, C. thyrsiflora, C. zuluensis and Neocussonia umbellifera are used as traditional medicines against 48 human and animal diseases. This study showed that alkaloids, anthocyanins, anthracene glycosides, botulin, flavonoids, free gallic acid, iridoids, phenolics, saponins, steroids, tannins, triterpenoids and volatile oils have been identified from these species. Pharmacological research revealed that the crude extracts and compounds demonstrated isolated from these species are characterized by Aβ42 protein reduction, acetylcholinesterase, analgesic, antibacterial, antifungal, antiviral, anticancer, antihyperglycemic, anti-inflammatory, antileishmanial, antioxidant, antiplasmodial, antiprotozoal, anti-ulcer, immunomodulatory, larvicidal, molluscicidal, spermicidal, cytotoxicity and toxicity activities. Reports of medicinal uses, phytochemistry, pharmacology and toxicological properties of species belonging to the family Araliaceae in southern Africa could only be found for 11 species, suggesting that further investigation of largely unexplored family members is necessary.